2016
DOI: 10.1002/jat.3417
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for direct effects of glyphosate on ovarian function: glyphosate influences steroidogenesis and proliferation of bovine granulosa but not theca cellsin vitro

Abstract: Glyphosate (GLY) is a common herbicide used worldwide but its effect on ovarian function in mammals is unknown. The aim of this study was to determine the potential endocrine disruptor effects of GLY on ovarian function evaluating cell proliferation, steroidogenesis and gene expression using bovine granulosa cells (GC) and theca cells as in vitro models. GC proliferation was impaired (P < 0.05) after exposure to GLY at 0.5, 1.7 and 5 μg ml . GC progesterone production was not affected (P ≥ 0.05) at all doses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 56 publications
(118 reference statements)
0
22
0
1
Order By: Relevance
“…and glyphosate exposure. In granulosa cells of bovine ovaries, however, exposure to glyphosate alone had no effect on either Cyp19a1 or Cyp11a1 [17].…”
Section: Accepted Manuscriptmentioning
confidence: 83%
See 1 more Smart Citation
“…and glyphosate exposure. In granulosa cells of bovine ovaries, however, exposure to glyphosate alone had no effect on either Cyp19a1 or Cyp11a1 [17].…”
Section: Accepted Manuscriptmentioning
confidence: 83%
“…A limited number of studies have reported disrupted hormone synthesis or signal transduction in various systems and, based on their findings, proposed that glyphosate is an EDC. These include the rat male reproductive organs [10][11][12] and adrenal gland steroidogenesis [13], as well as cell lines such as rodent Leydig cells [14,15], bovine granulosa cells [16,17], and human embryonic, placental and liver cells [18,19]. In many of these studies the tested substance was a commercial formulation of…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, various glyphosate formulations seem to have adverse effects on hormonal function, and it has been demonstrated that glyphosate-based herbicides, such as Roundup, have an impact on oxygen reactive species, and it also changes the redox system, resulting therefore in apoptosis [ 10 , 11 ]. Last, Roundup has been demonstrated to have deleterious effect on steroidogenesis and proliferation of bovine granulosa cells [ 12 ], indicating indirectly the impact of glyphosate on female gametes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…En lo que se refiere al glifosato, algunos estudios con ratas y células bovinas presentan evidencias de su toxicidad en relación con el sistema reproductivo (42)(43)(44). El estudio transversal de Garry et al (45) demostró mayor frecuencia de defectos congénitos en niños residentes del Valle del Río Rojo, Minnesota, una región de gran actividad agrícola de Estados Unidos.…”
Section: Discussionunclassified